Problems of Teachers and Santri in Learning the Qur’an - Fadhila Khairatun Nisa; Muhammad Ali Rido; Izharman Izharman (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2021)
This study aims to analyze the problems of teachers and students in learning the Qur'an. This study uses a qualitative method with a case study approach, data sources were taken from forty-two informants through in-depth interviews who were selected using a purposive sampling technique. All interview results were then analyzed thematically using Interactive Miles & Huberman's qualitative data analysis. The findings show that there are twelve findings of teacher and student problems in learning the Qur'an. Related to teacher problems include; i) lack of recitation and training activities for Al-Qur'an teachers, ii) lack of competency of the Qur'an teachers, iii) difficulty managing time, iv) class capacity of students, v) differences in student backgrounds, vi) organizing and conditioning students in class, vii) the lack of welfare of the teacher's Qur'an. Related to student problems; i) the level of student focus or concentration in learning, ii) lack of student discipline, iii) lack of student enthusiasm in learning. The research also found problems related to facilities and infrastructure, namely; i) lack of availability of the Qur'an, ii) lack of tables for the Qur'an.